The effectiveness of ozone therapy and carboxytherapy in aesthetic disorders: localized fat reduction and weight loss (Research, Society and Development, 2023)
The effectiveness of ozone on general health is evident around the world. With regard to the use of ozone therapy in aesthetic procedures, since the 2000s, extraordinary clinical effects have been determined in the literature, supporting the use of ozone in various aesthetic therapies. Another procedure that will be mentioned in this research is carboxytherapy, which is a little invasive procedure, with several benefits and few transversal effects. Objective: to analyze the effectiveness of Ozone therapy and carboxytherapy in aesthetic dysfunctions, emphasizing the reduction of localized fat and weight loss. Methodology: The research focuses on a literature review that was developed based on the synthetic reading of academic articles in relation to the theme addressed. With regard to the methodological processes, the bibliographical research used the main databases mentioned below: Google Scholar, SciElo, and LILACS. Discussions: With the research carried out, we can see that the results are effective as long as you have the continuous use of ozone therapy, such as the reduction of localized fat. Such works described that ozone has its functionality as a fantastic lipolytic agent, thus reducing adiposities with few applications. Therapy with carboxytherapy allows the evolution of blood and lymphatic flow, confers increased skin oxygenation and cellular nutritional development. Final Considerations: In the research carried out on the aesthetic procedures mentioned in the present work, we can emphasize that ozone therapy and carboxytherapy have satisfactory results for aesthetic dysfunctions, with emphasis on localized fat. The application of Ozone therapy in the treatment of aesthetic disorders provides excellent accessibility, as well as great benefits.